Disability Due to Traffic Accidents in Children and Affecting Factors - Yazıcı, Selçuk; Can, Muhammet (The Bulletin of Legal Medicine, 2019)
The word ‘Disability’ is defined injury. Road vehicles, related traffic accidents, accidents and deaths due to accidents are increasing day by day. 108 children aged 0-18 years were included in our study. Cases were divided into subgroups (G) according to age, G1 (0-6 years old pre-school group), G2 (7-12 age primary age group) and G3 (12-18 age group). Many parameters such as traffic accident type (in the vehicle, pedestrian, motorcycle), seat (front, back), fracture type and number of fractures were taken into consideration. The mean age of the children was 12.98 years (SD: 4,364 years). 68 were male (63.0%) and 40 were female (37.0%). The mean disability rate was 10.85% (range 2% to 59%). There was no difference between gender. 41 of the cases were in the vehicle, 35 were on motorcycles and 32 were pedestrians. The mean disability rate (27.13%, SD 27.77) was significantly higher in patients with open bone fractures compared to other fractures. Scoring systems, which are widely used at international level in the post-traumatic examination of pediatric patients, have not been introduced to general practice in our country yet. We believe that the use of scoring systems prepared or modified for children is important for treatment, for forensic reporting of children with sequelae due to traffic accident and aslo for their further life. Finally, how accurate is it that children are accepted as unskilled workers in disability calculations according to the regulations used in our country?